Exploring the Impact of Maternal Rejection on Emerging Adult Women - Nashwa Afifa Zahra; Satiningsih (Universitas Negeri Surabaya, 2026)
An insecure mother–daughter relationship resulting from maternal rejection can have long-term effects on the psychological development of emerging adult women. However, in-depth understanding based on subjective experiences remains limited. This study aims to explore the impact of maternal rejection through the lens of IPARTheory, focusing on how experiences of perceived rejection are interpreted, internalized, and carried into adulthood in this context. A qualitative phenomenological study was conducted with five women aged 20–30 years through semi-structured interviews and analyzed using Interpretative Phenomenological Analysis (IPA). Maternal rejection was interpreted as an insecure relational experience that affects relational conflict, ongoing internal conflict, physical condition, and parenting patterns, accompanied by the development of adaptive strategies by the participants. These findings underscore the significance of maternal rejection as a relational factor with enduring effects and highlight its importance in the context of psychological development and intervention. Abstrak Hubungan ibu–anak perempuan yang tidak aman akibat penolakan maternal dapat memiliki dampak jangka panjang pada perkembangan psikologis wanita dewasa muda. Namun, pemahaman mendalam berdasarkan pengalaman subjektif masih terbatas. Penelitian ini bertujuan untuk mengeksplorasi dampak penolakan maternal melalui lensa Teori IPAR, dengan fokus pada bagaimana pengalaman penolakan yang dirasakan diinterpretasikan, diinternalisasi, dan dibawa hingga dewasa dalam konteks ini. Penelitian fenomenologis kualitatif dilakukan dengan lima wanita berusia 20–30 tahun melalui wawancara semi-terstruktur dan dianalisis menggunakan Analisis Fenomenologis Interpretatif (IPA). Penolakan maternal diinterpretasikan sebagai pengalaman relasional yang tidak aman yang memengaruhi konflik relasional, konflik internal yang berkelanjutan, kondisi fisik, dan pola pengasuhan, disertai dengan perkembangan strategi adaptif oleh para peserta. Temuan ini menekankan pentingnya penolakan dari ibu sebagai faktor hubungan yang memiliki efek jangka panjang dan menyoroti pentingnya hal ini dalam konteks perkembangan psikologis dan intervensi.